Responsabilidade social nas agroindústrias canavieiras no Brasil. - Wissmann, Martin Airton (2017)
This research examines the social responsibility of the sugar cane industry in Brazil and analyzes how economic, environmental and social dimensions influence socially responsible behavior. A theoretical survey was carried out to identify origin, development and main concepts of social responsibility, pointing out its indicators, principal models and users and/or beneficiaries of social sustainability reports. Furthermore, the main theories related to socially responsible behavior were explored in order to support the composition of research tools and the analysis of results. The GRI-G4 model elaborated by the Global Reporting Initiative served as an additional resource. Purposing to show the relation between theme and object of this study, the sugar cane industry was characterized, presenting its economic, environmental and social impacts and further researches relating social responsibility and economic activity of this industry. The applied methodology consisted of explanatory, quantitative and qualitative research, utilizing questionnaires of a total population of 184 sugar cane industries (individuals or groups of companies), getting a return of 128, representing 5% margin of error and 96% confidence interval. In order to attest the hypothesis, modelling of structural equations by SmartPLS were applied. The results demonstrate that Brazilian sugar cane industry has reached an advanced stage in relation to the importance and practical accomplishment of the socially responsible actions raised by the research, but demonstrate the need to advance, mainly, the evidence of these actions. It also showed that the social dimension exerts major influence when compared to the other dimensions in the CSR.